Neuroendocrine responses to intravenous L-tryptophan in obsessive compulsive disorder. - Fineberg, N; Cowen, P; Kirk, J; Montgomery, SA (1994)
We studied the neuroendocrine responses produced by intravenous L-tryptophan (TRP) in 16 untreated patients with obsessive compulsive disorder (OCD) and 16 matched healthy controls. The increase in plasma growth hormone seen following TRP was significantly greater in the OCD patients, while TRP-induced prolactin release did not differ from controls. Taken in conjunction with findings from other neuroendocrine studies the data suggest that some aspects of 5-HT1A neurotransmission may be increased in OCD. This increase may represent a compensatory change which promotes adaptation to stress in non-depressed OCD patients.